2003
DOI: 10.1063/1.1581987
|View full text |Cite
|
Sign up to set email alerts
|

Photovoltaic effect on differential capacitance profiles of low-energy-BF2+-implanted silicon wafers

Abstract: Using scanning capacitance microscopy (SCM), we have studied the photovoltaic effect on differential capacitance (dC/dV) signals of low-energy-BF2+-implanted silicon wafers. The surface photovoltage induced by the stray light of the atomic force microscope laser beam leads to distorted dC/dV profiles and hence perturbs the contrast of SCM images. Due to the photovoltaic effect on the junction region, the observed junction image also exhibits a narrower junction width. According to this study, the photovoltaic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
13
1
Order By: Relevance
“…Indeed, when the laser was turned off using the "dark lift" mode, we did not observe any measureable affect on the SCM images, which is different from the literature 10,11 and is likely a result of a different sample setup. Intentionally connecting the contacts of a live device so that every local area of the front and back contacts are shorted could result in a different sample condition from an unintentionally, and unevenly, shorted device.…”
Section: Methodscontrasting
confidence: 50%
“…Indeed, when the laser was turned off using the "dark lift" mode, we did not observe any measureable affect on the SCM images, which is different from the literature 10,11 and is likely a result of a different sample setup. Intentionally connecting the contacts of a live device so that every local area of the front and back contacts are shorted could result in a different sample condition from an unintentionally, and unevenly, shorted device.…”
Section: Methodscontrasting
confidence: 50%
“…The measurement also shows a photovoltaic effect, evident in Fig. 9c where a short circuit current and an open circuit voltage can be observed, obtained by the contribution from the scattered light of the laser properly focused on the side of the AFM cantilever rear [36,37].…”
Section: Tuning the Dopant Distribution Propertiesmentioning
confidence: 76%
“…15 In 2003, Chang et al revealed that the laser beam in an atomic force microscope (AFM) may induce a photovoltaic effect on the SCM images, highlighting the influence of the SCM setup on the observation of EJ regions. 16,17 The SCS investigations by Buh et al indicated that both the AFM laser beam and the modulation voltage (MV) may distort SCS profiles of a metal-oxide-semiconductor (MOS) capacitor. 18 Moreover, the humidity-induced hysteretic behavior of SCS was studied, exploring the importance of environmental control for SCM measurements.…”
mentioning
confidence: 99%
“…According to prior reports, the commonly used peak-to-peak MV may range from 0.3 V to 5 V for the acquisition of SCM images of EJ regions. 5,6,11,16,17,20,21 However, a higher MV means that dC/dV signals are carried out from an extensively modulated area. This fact may perturb the SCM observation on EJ regions.…”
mentioning
confidence: 99%